Immobilization of Saccharomyces cerevisiae Cells on Luffa cylindrica: a Study of a Novel Material for the Adsorption of Textile Dye - Morão, Luana Galvão [UNESP]; Dilarri, Guilherme [UNESP]; Corso, Carlos Renato [UNESP] (My University, 2017)
The textile industry is responsible for the disposal of a large volume of effluents containing synthetic dyes, which are considered to be highly toxic compounds for both human health and the environment. The aim of the present study was to test potential use of a renewable, low-cost product—Luffa cylindrica in disk and powder form—as adsorbent material for the treatment of textile effluents containing dyes. Saccharomyces cerevisiae cells were also immobilized on L. cylindrica to increase the adsorbent capacity. Batch experiments were conducted for the evaluation of the removal of the azo dye Direct Red 23. The Langmuir, Freundlich, and Temkin isotherms were used for a better interpretation of the data. The results showed that adsorption is more efficient at acidic pH and all adsorbent materials best fit the Langmuir model, indicating the formation of a monolayer. The isotherm results also demonstrated that the materials immobilized with the yeast had a greater sorption rate, but the cell-free L. cylindrica powder had a higher adsorbate/adsorbent interaction. The comparison with a spectrophotometrically defined standard revealed that the powder without and with yeast cells was able to achieve an acceptable removal rate of the dye from the solution. Moreover, the difference in adsorption between the powder without and with yeast cells was very small. Thus, the application of the cell-free L. cylindrica powder is economically more feasible. The findings demonstrate the potential use of L. cylindrica powder as an adsorbent for the treatment of effluents containing textile dyes.
Keywords: Azo dye; Bioremediation; Isotherm; Luffa; Wastewater; Yeast